The Sosialisasi dan Simulasi Informasi Kebencanaan di SD Swasta Masehi Berastagi - Barus, Rehia K. Isabella; Dwiana , Ressi; Dewi, Salamiah Sari (Universitas Medan Area, 2024)
SD Swasta Masehi Berastagi is one of the elementary schools in Karo Regency. This school stands on a cliff so it is vulnerable to earthquakes or landslide. To help students and teacher to be aware of disasters, Medan Area University Service team offers to do socialization and also simulate disaster information in this elementary school. The partner in this program is the Karo Regency Disaster Management Agency (BPBD Karo). The aim of this program is to provide information dan simulations of disaster information to students trough song “Kalau Ada Gempa” dan cartoon film about action to do when earthquake. This activity was using presenting method which related to earthquake disaster information and simulating self-rescue when earthquake occurs. The simulazion was done by Karo Regency Disaster Management Agency. It is hoped that socialization and simulations can increase students’ insight and skills regarding earthquake disasters.